The Economic Impact of Military Expenditure and War on Ukraine’s Economic Growth (1990–2023) - Zaiets, Oleksandr (2025)
Abstract This bachelor’s thesis examines the economic impact of military expenditure and armed conflict on Ukraine’s GDP growth between 2014 and 2023, a period defined by prolonged warfare and substantial foreign aid. Using a mixed-methods approach, the study employs ordinary least squares (OLS) regression and Granger causality tests to analyse the effects of foreign aid, military spending, and conflict intensity on economic performance. The dataset is drawn from the World Bank, SIPRI, UCDP, and Antezza et al. (2025). The findings show no statistically significant impact of foreign aid or military expenditure on GDP growth. In contrast, conflict intensity—measured by battle-related deaths—has a strong and negative effect, underscoring the dominance of war’s destructive consequences over short-term fiscal stimulus. The thesis contributes to defence economics by addressing the understudied dynamics of ongoing war economies and offers policy insights for balancing security expenditures with economic recovery. Limitations include a small sample size (N = 9) and high multicollinearity, which constrain causal interpretation. The study recommends prioritizing infrastructure-focused aid to support long-term reconstruction and growth.